Micropropagation of Agave salmiana: Means to Production of Antioxidant and Bioactive Principles - Puente-Garza, César A.; Gutiérrez-Mora, Antonia; García-Lara, Silverio (Frontiers in Plant Science, 2015)
Maguey, Agave salmiana, is an important plant for the “pulque” beverage and functional food industries; however, it has several constraints for elite and homogeneous plant production. In this study, a micropropagation process was established to generate in vitro plants. The effect of the method on metabolite content and antioxidant (AOX) activity in regenerated plants was evaluated. Young germinated plantlets were micropropagated from axillary shoots using Murashige and Skoog medium supplemented with L2 vitamins, 0.04 mg/L 2,4-dichlorophenoxyacetic acid and 10 mg/L 6-benzylaminopurine. Total soluble sugars from the aqueous fraction and total phenolic acids, total saponins, and AOX activity of the methanol fraction were determined in wild type (WT) plants, in in vitro (IN) plants, and ex vitro acclimated plants (EN). The results showed that IN plants have a 50% lower soluble sugar content compared to WT and EN. The total phenolic acids content was at least 30% higher in micropropagated (IN) and regenerated (EN) plants compared to WT. The total saponin content in IN and EN plants was 36 and 25 times higher compared to WT. The AOX capacity of IN plants was on average three times higher compared to other treatments. However, no correlation was found between the AOX activity and total phenolic acids or total saponins. A negative and significant correlation (r = -0.927; p = 0.003) was found between the AOX activity and the total soluble sugars content. Micropropagated plants of A. salmiana have a different phytochemical content and bioactivity after the in vitro process compared to wild plants. The micropropagation process could be used as a platform for phytochemical enhancement of Agave plants.